Análise morfológica da evolução da reabsorção óssea à distância na movimentação dentária induzida em molares murinos - Cardoso, Lyzete Berriel (2010)
This study has as purpose to morphologically outline the evolution of the bone resorption at a distance, in the dental movement, induced in murine molar. The study also morphologically compared the events found in the periodontal ligament, in the root surface and on the bone surface of the periodontium of teeth submitted to light/moderate forces and to intense forces in the induced dental movement. For such, 24 rats of the lineage Wistar, of both gender were divided in groups, in accordance to the experimental period of 3, 5, 7 and 9 days. The device used for the dental movement was based on Heller and Nanda s model, with a closed stainless steel spring, anchored in the superior incisors, it was provoked the movement of mesio inclination of the first left maxillary first molar, applying a force of 75 cN. The qualitative microscopic analysis evaluated the tissue and cellular phenomena resulting from the dental movement of the mesiobuccal and distobuccal root, in transversal microscopic sections, in the different periods of observation. The roots of the right first molar, without dental movement, were used as control. The results of the analysis of the bone resorption analysis on distance showed that morphologically, it did not start in 3 days; only in 5 days bone modelling units installed in the peripheral of the hyaline area and on the surrounding bone surfaces; on the 7th day, it was organized and literally happening with the alveolar cortical bone, being destroyed; on the 9th day, it was still active, and the periodontal remodeling could be alleviated in a homogeneous and uniform way, and the associated root resorptions had maximum expression. The differences in the tissue and cellular reactions found on the mesiobuccal and distobuccal roots revealed to be statistically significant. Pursuant to the methodology used, it could be concluded that: 1. the observation periods in the experimental model of induced dental movement in rats, with the appliance was conceived by Heller and Nanda shall extend, as late as possible, after the 9th forces application day; 2: both roots analyzed represent distinct and consistent experimental models of observation of the reactions of the periodontal tissues, in view of light/moderate and intense forces, serving to test variables that may influence the induced dental movement.